Design of a circular dual‐loop antenna for a GPS array element using an extended cavity structure. Issue 4 (25th December 2018) - Hur, Jun; Byun, Gangil; Kim, JongSung; Kim, Misuk; Ko, Jinwon; Choo, Hosung
Abstract: This article proposes a circular dual‐loop antenna for a very small Global Positioning System array with an extended cavity structure. The antenna element consists of lower and upper circular loops printed on a high‐dielectric ceramic substrate and an extended cavity structure above the ground plane to improve the isolation characteristic. To demonstrate the suitability of the proposed antenna, antenna characteristics are measured in a full‐anechoic chamber, and its performances such as bore‐sight gain, mutual coupling, and near‐field as a function of extended cavity height are analyzed. The results confirm that the proposed antenna structure can minimize the gain degradation by improving the isolation characteristic and is therefore suitable for use in very small arrays.